Uso de plasma rico em plaquetas no tratamento de ulcerações corneanas superficiais em equinos - Karen Medina Teixeira (2014)
Diamond Burr debridement technique was evaluated for inducing superficial corneal ulcers, assessing its safety and standardization for the equine species. After validation, it was employed in the corneal ulcers experimental induction on eighteen horses eyes. Treatments with autologous and heterologous PRP were evaluated and compared to the positive (debrided eyes treated only with saline solution) and negative control groups (the left and non-debrided eye, receiving the same treatment applied in positive contralateral eye). Additionally, infrared ocular thermography was evaluated as a diagnostic feature of ulcerative keratitis in horses. The concordance rate among examiners when identifying ocular clinical signs was compared, pointing the difficulty in interpreting each of them. Diamond Burr debridement does not exceed the anterior stroma, being safe for superficial corneal ulcers experimental induction in horses. Clinical results were similar (p>0,05) among autologous and heterologous PRP groups. PRP use reduced 1,92 times the wound reparation period. Beneficial effects were similar in autologous and heterologous PRP groups and did not increase differently ocular inflammation. Ocular thermography was efficient in identifying 8,67 of 10 ulcerated eyes, being validated as effective screening feature for superficial ulcerative corneal wounds in horses. Corneal transparency, assessed 90 days after wound repair, was better preserved in animals treated with autologous PRP.